1999
DOI: 10.1093/emboj/18.23.6855
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid alteration (101L) introduced into murine PrP dramatically alters incubation time of transmissible spongiform encephalopathy

Abstract: A mutation equivalent to P102L in the human PrP gene, associated with Gerstmann-Straussler syndrome (GSS), has been introduced into the murine PrP gene by gene targeting. Mice homozygous for this mutation (101LL) showed no spontaneous transmissible spongiform encephalopathy (TSE) disease, but had incubation times dramatically different from wild-type mice following inoculation with different TSE sources. Inoculation with GSS produced disease in 101LL mice in 288 days. Disease was transmitted from these mice to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
173
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(180 citation statements)
references
References 50 publications
(66 reference statements)
6
173
0
1
Order By: Relevance
“…Targeted ES cells were used to generate chimeric mice as described previously (25) to obtain G1 and G2 heterozygous mice expressing mono-and unglycosylated PrP and G3 heterozygous mice expressing unglycosylated PrP. Heterozygous mice were bred to produce an inbred homozygous line.…”
Section: Generation Of Gene-targeted Micementioning
confidence: 99%
“…Targeted ES cells were used to generate chimeric mice as described previously (25) to obtain G1 and G2 heterozygous mice expressing mono-and unglycosylated PrP and G3 heterozygous mice expressing unglycosylated PrP. Heterozygous mice were bred to produce an inbred homozygous line.…”
Section: Generation Of Gene-targeted Micementioning
confidence: 99%
“…Some of these genetic diseases have been transmitted to primates or mice (6,7). De novo production of infectious prions from PRNP with point mutations would represent a useful tool for elucidating the origin of prion infectivity in genetic TSEs.…”
mentioning
confidence: 99%
“…Previous studies argued about a lack of correspondence between infectivity titers or disease severity and amount of PK-resistant PrP Sc . 18,19 In particular, Barron and coworkers demonstrated that tissues with very low levels of PK-resistant PrP Sc could be highly infective. 20 In this regard, the expression of scFvD18 could have hampered the formation of PK-resistant PrP Sc without interfering with an alternative PK-sensitive PrP Sc isoform.…”
Section: Distribution Of Aav9 In the Cnsmentioning
confidence: 99%